Computer Vision Based Intelligent 3D CNC Machines - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Innovative, digital, embedded processing units and systems and easy-to-use design tools help deliver the digitalization of systems to enable smarter, safer, more efficient machines and factories. All these new technologies and innovations help us to design what's new and what's next in industrial processing, monitoring, sensing, command and control, communication, functional safety and power management. This study presents a collection of practical applications of computer vision and a plan to prepare utility software, which is based on latest technology of computer vision, which makes easy to prepare a CAD drawing from an image for CNC machines. This method could be useful in the field of reverse engineering for reproducing existing products which has not a vector drawing or the restoration of a historical item. © 2020 IEEE.
Keywords: Computer Numerically Controlled Machines.; Computer Vision; Machine Vision; Smart Factories; Smart Machines